Cadmium Contents in Water and Tilapia (Oreochromis niloticus) in Telaga Tunjung Dam, Tabanan, Bali - Jozze Brendo Simanjuntak; Alfi Hermawati Waskita Sari; Ayu Putu Wiweka Krisna Dewi (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2025)
Agricultural activities around the Telaga Tunjung Dam also have the potential for the entry of heavy metal cadmium (Cd) into the water and accumulate in aquatic organisms, especially in fish. The presence of cadmium (Cd) in water and fish that exceeds the limit can have a negative impact on human health. The purpose of this study was to determine the cadmium (Cd) content in water and tilapia that had been caught in the Telaga Tunjung Dam. The study was conducted at the Telaga Tunjung Dam from February to March 2023. The research method used was a comparative descriptive method. The highest cadmium (Cd) content in water was detected at station IV, which was 0.078 mg/l. Cadmium (Cd) content was also detected in tilapia liver at 1.043 mg/kg, and the highest cadmium (Cd) content was detected in tilapia meat at 1.541 mg/kg. These values ​​have exceeded the quality standard threshold set by Bali Governor Regulation No. 8 of 2007 (0.01 mg/l), and SNI 7387:2009 for the fish and processed fish category (0.1 mg/kg). Meanwhile, the results of measurements of dissolved oxygen (DO), temperature and pH are still optimal and support the life of aquatic organisms.